Putničko brodarstvo - TAUZOVIĆ, Jovo (Promet - Traffic&Transportation, 2026)
PASSENGER SEA-FARING FLEET The author states that the passenger sea-faring fleet provides passenger services on scheduled routes, cruises and ferry-boat lines. On the side of supply we have passenger shipping companies, passenger shipping conferences and a large variety of travel agent networks all over the world, while on the side of demand for the most part we deal with holiday-makers or vacationers and excursionists. The paper specifically reviews the issues of cost-fixing.